Letter (copy) : Basque Children - Tewson, Vincent
1939-10-17 038-0072-001 International HVT/AC/21 17th October, 1939. Mr. Will F. Maw, Leicester & District Trades Council, 11, Chepstow Road, LEICESTER Dear Mr. Maw, BASQUE CHILDREN. Mr. Wray has handed to me your letter of 14th October on the question of the Basque refugee children in this country. I happen to be on the National Committee of the Basque Children's Fund. You may rest assured that the Committee is pursuing the question of the maintenance of these children from many angles, as it is becoming increasingly difficult to secure funds. Of the four thousand children who originally came, only a thousand now remain, and it is likely that, as soon as transport can be secured, about 400 of these will return. This leaves us with a problem of about 600 children, whose parents are, in the main, in France and are themselves refugees. There are other minor categories also, where the National Committee feel that it is impracticable for the children to return. Many consultations are taking place on this question, but you may rest assured that everything possible is being done to secure a satisfactory settlement of the position. A separate letter will be sent to you with regard to the points about the Court of Referees and transference of labour. Yours sincerely, Assistant Secretary. 292/946/38/72(I)